Sexual and gender minority health - LeBlanc, Allen J.; Perry, Brea L. (Advances in medical sociology, 2021)
This volume of Advances in Medical Sociologyshowcases rich theoretical and empirical contributions on SGM health and wellbeing. The chapters address a variety of topics, drawing from classic and contemporary sociological frameworks and constructs, and reflecting intersecting interdisciplinary approaches to SGM health.